The role of green energy, globalization, urbanization, and economic growth toward environmental sustainability in the United States - Raihan, Asif; Atasoy, Filiz Guneysu; Atasoy, Murat; Ridwan, Mohammad; Paul, Arindrajit (Journal of Environmental and Energy Economics, 2022)
The subject of global climate change is of great concern due to the accumulation of greenhouse gases (GHGs) in the atmosphere, primarily carbon dioxide (CO2). The United States ranks as the second-largest contributor to CO2 emissions globally, accounting for almost 15% of the total global emissions. The primary contributor to the United States' emissions is the combustion of fossil fuels to generate power, provide heat, and facilitate transportation. Nevertheless, the United States intends to decrease emissions by substituting fossil fuels with ecologically sustainable green energy sources. This study aims to analyze the effects of green energy consumption, economic growth, globalization, and urbanization on CO2 emissions in the United States. It utilizes annual time series data from 1970 to 2022. The Autoregressive Distributed Lag (ARDL) predictions indicate that a 1% increase in green energy and globalization would result in a reduction in CO2 emissions by 0.44% and 0.61% in the short term, and by 0.76% and 1.45% in the long term. Nevertheless, there is a direct correlation between a 1% rise in economic growth and urbanization and a corresponding increase in CO2 emissions. Specifically, in the short-term, CO2 emissions increase by 0.59% and 0.56%, while in the long-term, the increase is 0.29% and 0.20%. The findings validate the urgent need for a higher proportion of renewable energy in the energy mix. To achieve this, it would be necessary to promptly increase the renewable portfolio standards besides implementing additional aggressive cleaner energy goals. Furthermore, it is imperative to advocate for the promotion of sustainable trade performance besides fostering global partnerships with different nations to facilitate the development of collaborative research initiatives, sharing of specialized knowledge, and stimulation of innovation in the fields of green energy and sustainable practices.